Speciation of cadmium, copper, lead and zinc in the waters of River Mzimbazi Dar es Salaam, Tanzania - OC Othman, OC Othman (Tanzania Journal of Science, 2021)
The water of river Mzimbazi and its attributaries are known to contain heavy metals originating from industry and the water is used for domestic and vegetable irrigation purposes. The present study describes chemical forms of some of the heavy metals found in the water. Water samples from different locations along river Msimbazi were analysed by Differential Pulse Anodic Stripping Voltammetry (DPSAV) based on an operational scheme for the determination of the chemical forms of dissolved copper, lead, cadmium and zinc. Zinc (82%), cadmium (73%) and copper (93%) were found to exist mainly as soluble metal ions while lead existed as moderately soluble ions (<60%). On the average, 40% of the lead was found complexed to the filterable contents of the water as compared to only 6.6% of the copper, 17.5% of the zinc and 26.3% of the cadmium. Thus membrane filtration was able to remove quite a large amount of pollutants. The lability of the lead (52.6%) in raw river water, was lower than that of zinc (61.6%), copper (65.4%) and cadmium (61%). The lability of the lead (38%) in filtered water, was also lower than that of zinc (51.9%), copper (63.7%) and cadmium (48.8%). In raw river water, cadmium had the lowest ASV lability (42.0%) as compared to zinc (48.4%), copper (50.7%) and lead (47.4%) whereas in filtered water the ASV lability of lead (29.3%) was the lowest; those of zinc (37.6%), copper (45.4%) and cadmium (40.8%) were much higher. A high percent of the labile trace lead (27.8%), cadmium (20%) and zinc (15.7%) and only 2.6% of the labile copper adhere to the filterable content of the water thus may be filtered off.